A smelting–rolling strategy for ZnIn bulk phase alloy anodes. Issue 39 (28th September 2022) - Chai, Yizhao; Xie, Xuesong; He, Zhangxing; Guo, Guangyi; Wang, Pinji; Xing, Zhenyue; Lu, Bingan; Liang, Shuquan; Tang, Yan; Zhou, Jiang
Abstract : A ZnIn alloy anode with trace indium is obtained by smelting–rolling method. The Zn deposition could be regarded as instantaneous nucleation that can alleviate the effect of deposition layer for the diffusion zone and suppresses dendrite growth. Abstract : Reversibility and stability are considered as the key indicators for Zn metal anodes in aqueous Zn-ion batteries, yet they are severely hindered by uncontrolled Zn stripping/plating and side reactions. Herein, we fabricate a bulk phase ZnIn alloy anode containing trace indium by a typical smelting–rolling process. A uniformly dispersed bulk phase of the whole Zn anode is constructed rather than only a protective layer on the surface. The Zn deposition can be regarded as instantaneous nucleation due to the adsorption of the evenly dispersed indium, and formation of the exclusion zone for further nucleation can be prevented at the same time. Owing to the bulk phase structure of ZnIn alloy, the indium not only plays a crucial role in Zn deposition, but also improves the Zn stripping. Consequently, the as-designed ZnIn alloy anode can sustain stable Zn stripping/plating for over 2500 h at 4.4 mA cm −2 with nearly 6 times smaller voltage hysteresis than that of pure Zn. Moreover, it enables a substantially stable ZnIn//NH4 V4 O10 battery with 96.44% capacity retention after 1000 cycles at 5 A g −1 . This method of regulating the Zn nucleation by preparing a Zn-based alloy provides a potential solution to the critical problem of Zn dendrite growth and by-product generation fundamentally.